Particles in teaching south Slavic languages - Virna Karlić; Jelena Tušek (Opera slavica, 2014)
This paper deals with the position and treatment of particles in teaching South Slavic languages. The first part of the paper is dedicated to theoretical and methodological problems related to the interpretation of particles and to the way they are reflected in teaching and in language handbooks. The second part demonstrates how to define and classify particles in selected grammar books of the South Slavic languages, while the final chapters are dedicated to an analysis of marking particles in dictionaries and to their treatment in foreign language textbooks.